2014
DOI: 10.1002/acr.22371
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Physician Expectations of Add‐On Treatment With Golimumab for Rheumatoid Arthritis: Relationships Between Expectations and Clinical and Quality of Life Outcomes

Abstract: Objective. Rheumatoid arthritis (RA) management involves improving clinical outcomes and quality of life (QOL).Golimumab is used as add-on therapy for patients who have failed disease-modifying antirheumatic drugs (DMARDs). This GO-MORE subanalysis investigated relationships between patient and physician expectations and outcomes. 43); 95.9% expected golimumab to be better than current treatment. Patients with fewer DMARD failures, higher disease activity, shorter disease duration, younger age, and female sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…However, other real-world studies have suggested that retention is at least as good, and possibly better, with golimumab than with some other TNFα inhibitors over 3 years [5,21]. Low immunogenicity, good tolerability with a very low percentage of injection-related side effects and ease of use (1-month dosing and easy-touse device) can account for better patient acceptance of the drug and, ultimately, high golimumab retention rates [22]. In the current study, regression analysis confirmed that the probability of continuing treatment with golimumab was higher when it was used as the first biological agent rather than as second-or third-line/later biological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, other real-world studies have suggested that retention is at least as good, and possibly better, with golimumab than with some other TNFα inhibitors over 3 years [5,21]. Low immunogenicity, good tolerability with a very low percentage of injection-related side effects and ease of use (1-month dosing and easy-touse device) can account for better patient acceptance of the drug and, ultimately, high golimumab retention rates [22]. In the current study, regression analysis confirmed that the probability of continuing treatment with golimumab was higher when it was used as the first biological agent rather than as second-or third-line/later biological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients’ high expectations may be shaped by general optimism, attitudes, and advertisements or other media representations. Although HCPs may generally anticipate that a medication will be effective, their expectations may be refined by considering individual patient characteristics such as age and disease severity [ 15 ]. This discrepancy of efficacy expectations between consumers and HCPs may be an additional reason relatively more DI reports were submitted by consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Although AUC in the ROC analysis of the prediction models was relatively high, not all factors that may affect response were included in the model. For example, patient expectations about effectiveness of treatment have been shown to be associated with remission [ 20 ]. The very large patient numbers are a clear strength of this analysis.…”
Section: Discussionmentioning
confidence: 99%